Isolation of B-cells using Miltenyi MACS bead isolation kits. - Dannielle K Moore; Bongani Motaung; Nelita du Plessis; Ayanda N Shabangu; André G Loxton; SU-IRG Consortium (PLoS ONE, 2019)
This article describes the procedures used to isolate pure B-cell populations from whole blood using various Miltenyi magnetic-activated cell sorting (MACS) bead Isolation kits. Such populations are vital for studies investigating the functional capacity of B-cells, as the presence of other cell types may have indirect effects on B-cell function through cell-cell interactions or by secretion of several soluble molecules. B-cells can be isolated by two main approaches: 1) Negative selection-in which B-cells remain "untouched" in their native state; this is advantageous as it is likely that B-cells remain functionally unaltered by this process. 2) Positive selection-in which B-cells are labelled and actively removed from the sample. We used three Negative B-cell isolation kits as well as the Positive B-cell isolation kit from Miltenyi and compared the purity of each of the resulting B-cells fractions. Contamination of isolated B-cell fractions with platelets was the conclusive finding for all of the isolation techniques tested. These results illustrate the inefficiency of current available MACS B-cell isolation kits to produce pure B-cell populations, from which concrete findings can be made. As such we suggest cell sorting as the preferred method for isolating pure B-cells to be used for downstream functional assays.